Effect of regional block technique on postoperative high-grade complications according to Clavien-Dindo classification in elderly patients with thoracic and abdominal cancer: a retrospective propensity score matching analysis - Ding, Weisi; Zhang, Yunpeng; Liu, Huixin; Zhou, Tianxin; Zhao, Wanlu; Feng, Yi; An, Haiyan (Frontiers in Oncology, 2023)
Background Postoperative complications have an influence on postoperative rehabilitation, length of hospital stay and hospitalization expenses in elderly patients, especially those with higher Clavien-Dindo (C-D) classification. Patients with cancers often experience more serious postoperative complications after surgery. Different anesthesia methods can affect the postoperative outcomes of cancer patients. Regional block techniques have been recommended in guidelines for enhanced recovery after surgery. However, the relationship between regional blocks and high-grade postoperative complications remains unclear, thus, the study explored the relationship between regional block techniques and high-grade postoperative complications graded by C-D classification in elderly patients with thoracic and abdominal cancer. Method Retrospective enrollment of eligible elderly patients admitted to Peking University People’s Hospital between January 2018 and March 2022 was conducted. Propensity score matching (PSM) and univariate and multivariate regression analyses were used to analyze the potential benefits of regional blocks for elderly patients in real world practice. Results A total of 2769 patients were enrolled in this study, including 568 who underwent colorectal resection, 2201 who underwent video-assisted thoracoscopic pneumonectomy. Among them, 2033 patients received regional block, while 736 patients did not. Statistical analysis indicated that regional blocks could reduce the incidence of postoperative complications of C-D classification Grade II or higher, with an Odds ratio (OR) of 0.742, 95% Confidence interval (CI) (0.552 to 0.996) (P = 0.047). Conclusion Regional block is associated with a reduction in the occurrence of postoperative complications graded by C-D classification in elderly patients with thoracic and abdominal cancer. The application of regional blocks can lower the risk of high-risk complications and mortality.